2014
DOI: 10.1088/1612-2011/11/6/065602
|View full text |Cite
|
Sign up to set email alerts
|

Label-free identification of intestinal metaplasia in the stomach using multiphoton microscopy

Abstract: The early diagnosis of intestinal metaplasia (IM) in the stomach together with effective therapeutic interventions is crucial to reducing the mortality-rates of the patients associated with gastric cancer. However, it is challenging during conventional white-light endoscopy, and histological analysis remains the ‘gold standard’ for the final diagnosis. Here, we describe a label-free imaging method, multiphoton microscopy (MPM), for the identification of IM in the stomach. It was found that multiphoton imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 56 In comparison, TPEF has higher optical sectioning ability but less photobleaching and photodamaging to the intestinal tract of mice. 56 In another study, Wu et al 57 identified goblet cells by imaging normal and intestinal gastric tissues using TPEF. They suggested that normal gastric tissues and intestinal gastric tissues can be distinguished by calculating the total number of goblet cells per unit area, that is, the density of goblet cells.…”
Section: Application Of Mpm In Study Of Gastric Tumorsmentioning
confidence: 99%
“… 56 In comparison, TPEF has higher optical sectioning ability but less photobleaching and photodamaging to the intestinal tract of mice. 56 In another study, Wu et al 57 identified goblet cells by imaging normal and intestinal gastric tissues using TPEF. They suggested that normal gastric tissues and intestinal gastric tissues can be distinguished by calculating the total number of goblet cells per unit area, that is, the density of goblet cells.…”
Section: Application Of Mpm In Study Of Gastric Tumorsmentioning
confidence: 99%
“…Many studies have showed its ability in the detection of digestive tract diseases with high resolution and high sensitivity [8,9]. However, previous publications mainly focused on the identification of pathological changes in gastrointestinal diseases such as stromal fibrosis, intestinal metaplasia, and so on [10][11][12]. To the best of our knowledge, there were no reports about how to use this imaging technique for assessing the surgical margin.…”
Section: Introductionmentioning
confidence: 99%